Evaluasi HbA1c, hs-CRP, dan indeks massa tubuh pada populasi sehat: Sebuah studi komunitas - Arum Tri Wahyuningsih; Fuad Anshori; Elizabeth Henny Herningtyas; Tri Ratnaningsih (Journal of Community Empowerment for Health, 2019)
Insulin resistance as a cause of type 2 diabetes mellitus is associated with subclinical inflammatory processes. Insulin resistance with obesity, hypertension, and dyslipidemia contribute to metabolic syndrome that increased risk of cardiovascular disease. High sensitivity C-reactive protein (hs-CRP) is an inflammatory marker that is thought to be associated with both type 2 diabetes mellitus and cardiovascular disease. This study evaluated hs-CRP, HbA1c, and body mass index in a healthy community. This cross-sectional study is an observational analytic study evaluating the association between hs-CRP, HbA1c, and body mass index. The research subjects were all healthy on a community gathering in community service programs, and if there were any signs or symptoms of infection or inflammation, they would be excluded. Measurements of hs-CRP and HbA1c were carried out using the HPLC and ELISA methods, respectively. The measurement results were analyzed to evaluate the characteristics of the subject and assess the relationship between the parameters studied with different mean and correlation tests. In 25 subjects involved, it was found that 96% had an HbA1c value of <6.5% with a normal body mass index of 15 subjects (60%), and the rest were in the category of overweight. The median hs-CRP level was 2.99 mg / L (0.81-13.74 mg / L), with a low heart risk category of only 4% of all study subjects. There was no correlation between hs-CRP with HbA1c (r = 0.35; p = 0.868) and body mass index (r = 0.37; p = 0.069). Only one subject was included in the diabetes diagnostic criteria, but 96% of the study population had hs-CRP, which was included in the medium-risk and high-risk category for heart disease. There was no association between hs-CRP and HbA1c and body mass index in healthy populations in this community.